Tetrahydrocannabinolic Acid Synthase, the Enzyme Controlling Marijuana Psychoactivity, is Secreted into the Storage Cavity of the Glandular Trichomes - Sirikantaramas, S.; Taura, F.; Tanaka, Y.; Ishikawa, Y.; Morimoto, S.; Shoyama, Y.
Tetrahydrocannabinolic acid (THCA)synthase is the enzyme responsible for the production of tetrahydrocannabinol (THC), the psychoactive component of marijuana (Cannabis sativa L.). We suggest herein that THCA is biosynthesized in the storage cavity of the glandular trichomes based on the following observations. (i)The exclusive expression of THCA synthase was confirmed in the secretory cells of glandular trichomes by reverse transcription- PCR (RT-PCR)analysis. (ii)THCA synthase activity was detected in the storage cavity content. (iii)Transgenic tobacco expressing THCA synthase fused to green fluorescent protein showed fluorescence in the trichome head corresponding to the storage cavity. These results also showed that secretory cells of the glandular trichomes secrete not only metabolites but also biosynthetic enzyme.
Keywords: BIOSYNTHESIS; GLANDULAR TRICHOME; LOCALIZATION; MARIJUANA; TETRAHYDROCANNABINOL; TETRAHYDROCANNABINOLIC ACID SYNTHASE